2019
DOI: 10.1002/ejsp.2639
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the facets of the big two in global evaluation of self versus other people

Abstract: The Big Two of agency and communion can be divided into the facets of agency‐assertiveness, agency‐competence, communion‐morality, and communion‐warmth. The present research studies how these facets are related to global evaluation of self versus others. In five studies we tested whether self‐evaluation is reliably related to agency‐assertiveness (H1), and evaluation of others to communion‐morality (H2). Participants had to describe themselves (or a specific other person) on the facets and later to rate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…However, while this instruction indisputably could have led participants to use the attribute 'honest' more often, it is not probable that this example led them to name more communal than agentic words in general. The attribute 'honest' falls within the morality facet of communion, whereas other frequently named communal words in our study were related to warmth, e.g., 'nice', 'helpful', 'friendly', 'polite' and 'animalloving' (Abele & Hauke, 2019;Abele et al, 2016). Third, the students were asked to describe themselves using a maximum of three attributes, which might restrict the scope of our data.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, while this instruction indisputably could have led participants to use the attribute 'honest' more often, it is not probable that this example led them to name more communal than agentic words in general. The attribute 'honest' falls within the morality facet of communion, whereas other frequently named communal words in our study were related to warmth, e.g., 'nice', 'helpful', 'friendly', 'polite' and 'animalloving' (Abele & Hauke, 2019;Abele et al, 2016). Third, the students were asked to describe themselves using a maximum of three attributes, which might restrict the scope of our data.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…Communionoriented individuals describe themselves in expressive terms by referring to their relationships with others and their sense of belonging, while agency-oriented individuals describe themselves instrumentally in view of their individual accomplishments and capabilities (Abele et al, 2016;Bakan, 1966;Diehl et al, 2004). Recent research has demonstrated that agency and communion further subdivide into different facets, with agency composed of assertiveness and competence and communion composed of warmth and morality (Abele & Hauke, 2019). However, agency and communion are more than just dimensions of people's selfdescriptions -they also have implications for social functioning, health, and well-being (Helgeson, 1994).…”
mentioning
confidence: 99%
“…A final issue concerns the facets of the Big Two (Abele et al, 2008b; Abele & Hauke, 2019; Abele et al, 2016). In all three experiments, our measures tapped the agency‐assertiveness and the communion‐friendliness facets, but not the agency‐ability and communion‐morality facets.…”
Section: Discussionmentioning
confidence: 99%
“…The agentic facets are competence and assertiveness, as "getting ahead" requires both skill (competence) and motivation/ volition (assertiveness). Regarding communion, research has shown that morality plays a more central role in the evaluation of groups and individuals than warmth (Abele and Hauke 2019;Abele 2019, 2020a, b;Leach et al 2007;review: Brambilla and Leach 2014). Regarding agency, first empirical evidence shows that ascribed status is more related to assertiveness than to competence (Carrier et al 2014;Louvet et al 2019) as is self-esteem (Abele et al 2016;Hauke and Abele 2020a, b).…”
Section: Basic Dimensions Of Social Perception: Communion and Agencymentioning
confidence: 99%